TINGKAT KENYAMANAN RUANG TERBUKA HIJAU (RTH) PERUM BUMI WAY URANG KALIANDA - Enda Susianti; Rudi Hilmanto; Rahmat Safe’i (Lambung Mangkurat University-Indonesia, 2020)
Kalianda is the capital of South Lampung Regency which has 4 city parks. One of the city parks is an area of Green Open Space (RTH) known as RTH Perum Bumi Way Urang. RTH is located in a housing complex, so it becomes a place for social interaction of local people, as well as places for other creatures to live and develop sustainably. However, the assessment of the comfort of RTH is unknown. The convenience of green space is important in maintaining the balance of community activities. The purpose of this study was to determine the comfort level of open green perum Bumi Way Urang Kalianda. The importance of this research as a reference for the government in planning and to make the decision to develop Perum Bumi Way Urang open green space is ideal and comfortable. The method used to determine the comfort level of open green space is the Temperature Humidity Index (THI) method and the percentage of canopy density. The data measured is temperature and humidity using a thermohigrometer and canopy density using the Habitapp application. The results showed that the comfort level of RTH Perum Bumi Way Urang based on the temperature and humidity index in the morning and evening was moderate with a value (THI = 23-27), during the daytime it showed a value (THI => 27) that is uncomfortable. It is necessary to add tree species that have a tight canopy, so that these conditions can make the visiting community feel comfortable.